TA’LIM TIZIMIDA SUN’IY INTELLEKT TEXNOLOGIYALARINI JORIY ETISH TAJRIBALARI - Radjabov Bunyod Abduxalilovich (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This article analyzes the international experiences of integrating Artificial Intelligence (AI) technologies into higher education systems, focusing on the cases of the United States, China, and Finland. The study explores the role of AI in digital transformation of education, improving institutional management, enhancing teachers’ productivity, and personalizing students’ learning paths. It also examines global frameworks and policy initiatives from UNESCO, OECD, and McKinsey Global Institute to identify adaptable approaches for Uzbekistan’s higher education context. The results confirm that AI technologies positively affect the quality of education, cost efficiency, and institutional performance in the context of digital economy.